2014
DOI: 10.1002/aehe.20018
|View full text |Cite
|
Sign up to set email alerts
|

Student Engagement in Online Learning: What Works and Why

Abstract: OverviewW ITH PRESSURES TO INCREASE ACCESS to higher education, colleges and universities have focused on increasing the number of online courses and programs offered. Higher education is also being criticized for its retention and graduation rates, and pressure is building to find solutions. To ensure that online learning can help address these problems, professionals dedicated to online learning are under pressure to explore and evaluate strategies for getting students engaged in their online studies. These … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
133
0
6

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 194 publications
(144 citation statements)
references
References 135 publications
(207 reference statements)
5
133
0
6
Order By: Relevance
“…While some students wish to engage in high level thinking, others reject this type of learning activity (Hall, 2015;Meyer, 2014). Stein, Wanstreet, Slagle, Trinko, and Lutz (2013) found that the use of coaching by the instructor and feedback from the instructor increased high-level thinking in online class discussions.…”
Section: Levels Of Questioningmentioning
confidence: 99%
See 3 more Smart Citations
“…While some students wish to engage in high level thinking, others reject this type of learning activity (Hall, 2015;Meyer, 2014). Stein, Wanstreet, Slagle, Trinko, and Lutz (2013) found that the use of coaching by the instructor and feedback from the instructor increased high-level thinking in online class discussions.…”
Section: Levels Of Questioningmentioning
confidence: 99%
“…When they are working a full time job, dealing with family commitments, and taking online classes, time can be a scarce commodity. Some individuals overcome their personal circumstances and graduate with their degree (Meyer, 2014). However, a lack of time due to variables such as work commitments or family commitments leaves them with less time to participate in online discussions (Fung, 2004;Gerbic, 2006;Hammond, 1999;Hew & Cheung, 2010a;Jeong & Frasier, 2008;Norton & Hathaway, 2008;Rollag, 2010), can negatively impact their ability to learn the coursework (Fisher, 2010;Meyer, 2014), and can lead them to withdraw from online courses (Bonk & Khoo, 2014;Hartnett, 2016).…”
Section: Cognitive Presencementioning
confidence: 99%
See 2 more Smart Citations
“…Despite challenges, e-learning continues to become increasingly popular in tertiary institutions and numerous studies contend that technology improves interactivity and results in effective learning for online students (Cheok & Wong, 2015;Cradduck, 2012;Meyer, 2014;Rivers, Richardson, & Price, 2014;Wei et al, 2015). This division in the literature about the benefits and challenges associated with elearning led the authors to inquire, "What factors determine whether e-learning will be effective in multilocation group settings?"…”
mentioning
confidence: 99%